Design and study on fault tolerant permanent magnet starter-generator for more electric aircraft application - Wang, Bo (2023)
The implementation of a permanent magnet electrical machine is a very attractive candidate for aircraft industry, especially which applications need high power density and high efficiency. Besides, achieving such objectives while pursuing high reliability is very challenging and requires an optimal machine design with robust solutions for fault tolerance. To address these aspects, this thesis aims to utilize a novel fault tolerant topology through detailed comparisons, verifying fundamental performance and fault tolerance. To achieve this goal, the first stage of the project involves the comprehensive review in aircraft electrification and the state-of-art fault tolerant approaches for permanent magnet synchronous machine. The second stage has shown the initial design of the feasible candidates, with multiple objective optimization design process and validation of fault tolerance. The third stage consists of thermal management, mechanical design and final electromagnetic design. All the details of this optimal candidate are sorted out. A prototype machine based on the optimal candidate of this project is manufactured and experimentally tested. The main contribution of this work is the investigation and verification of a feasible design process and novel topology for safety-critical application applied on aircraft due to 1) multiple objective and multiple discipline design process 2) the proposed novel topology for the improvement of fault tolerance. This knowledge is then used to inform future machine designers on how to take these aspects into consideration during the design of electrical machines.